An Electrochemical Effectiveness Model and Its Implication for Performance Loss Due to Electrode Microstructural Degradation in Solid Oxide Fuel Cells. Issue 5 (18th July 2016) - Baek, S. M.; Shin, D.; Sohn, S.; Nam, J. H.
Abstract: The electrochemical performance of solid oxide fuel cells (SOFCs) is known to depend strongly on the electrode microstructure. Based on the electrochemical effectiveness model recently explored by the authors, this study proposes a theoretical model for the reduction of current generation performance due to microstructural degradation. The effects of the three‐phase boundary length (TPBL) and the effective ionic conductivity are predicted for three distinct operating regimes: low (<0.05), intermediate (0.5–2), and high (>3) Thiele moduli. Numerical experiments are performed to simulate the performance loss due to electrode degradation using polarization resistances derived from experimental studies, the results of which are compared with the predictions of the theoretical model to investigate its reliability.